El relevo generacional y el crecimiento de las empresas familiares en la ciudad de Trujillo – 2019 - Ruiz Tacanga, Ruth Bethy (2020)
This research work was developed in order to know the impact of generational relevo on the growth of family businesses in the city of Trujillo in 2019. For this purpose, an explanatory–transferal field research was carried out with two variables: generational re-relay and growth of family companies, as well as the following methods: analytical, inductive and synthetic. Also, as a qualitative investigation, data collection was carried out through the survey technique, which was applied to the current successors of family businesses. The research concluded that generational relevo has a positive impact on the growth of family businesses in the city of Trujillo, as organizations that perform a planned generational relay, record stronger growth factors than those that go through this process empirically. Despite this, Trujillo's micro and small family businesses have only levels of growth ranging from mild, moderate to moderately high, this is usually due to the founders' reluctance to retire or the lack of preparation of a long-term strategic plan by current successors to face generational respite. For this reason, the future of the organization ends up in the hands of chance and improvisation, factors that eventually lead the family organization towards its disappearance.